Analysis of Determinant Factors Affecting Work Discipline - Feranita, Nungky Viana; Ardianto, Widi (Institut Teknologi dan Sains Mandala, 2025)
Fingerprints, sanctions, and motivation all play a crucial role in enhancing employee work discipline. This study aims to analyze the direct influence of these three variables on work discipline. The study was conducted at PT. Arista Jaya Lestari (Wuling Motor Probolinggo Dealer). This study is a quantitative study with a causal associative type. The population is all employees and the sampling technique uses saturated samples so that the number of respondents is 33 people. The main data source of the study was obtained from distributing questionnaires to employees. Multiple linear regression analysis was used to determine the direct influence using SPSS 26 software. The results of the study show that fingerprints, sanctions, and motivation simultaneously influence work discipline. Partially, fingerprints and motivation do not influence work discipline, while sanctions are the only variables that influence work discipline. These results provide practical implications for PT. Arista Jaya Lestari to increase the imposition of sanctions on employees so that they can help in increasing their work discipline. These sanctions can be preventive or repressive sanctions.